Temperature regulation of Heterotrigona itama (Cockerell, 1918) in lamp posts nests - Florina Anthony; S. H. Yek (Birkhauser Verlag Ag., 2025)
The commercial stingless bee Heterotrigona itama naturally nests in tree cavities but is kept in wooden boxes in meliponiculture farms. However, at Universiti Malaysia Sabah (UMS), these bees primarily nest in lamp posts. We conducted a temperature survey to investigate the potential infuence of temperature on the selection of lamp posts as nesting sites by H. itama. We measured ambient temperatures in occupied lamp posts in shaded areas and unoccupied lamp posts in exposed areas on the UMS campus, calculating the percentage of time these temperatures fell outside the optimal range for H. itama. Our aim is to determine if the preference for occupied lamp posts was related to their distribution in relation to temperature variations. In addition, we analyzed the occurrence and timing of temperature regulation in lamp post nests by comparing temperature diferences between occupied and unoccupied lamp posts across four-time blocks. Temperature measurements of occupied (shaded) and unoccupied (exposed) lamp posts revealed that exposed lamp posts experienced maximum temperatures outside the bees’ optimal range (27–32 °C), unlike the shaded lamp posts. The percentage of time that temperatures exceeded the optimal range was 9.72% higher for exposed lamp posts compared to shaded lamp posts. This suggests that H. itama may prefer shaded lamp posts due to their more stable temperature profle. The inside temperature of lamp posts, whether occupied or not, was consistently 1.54–1.76 °C warmer than ambient during hotter periods and closer to ambient during cooler periods, indicating conductive properties of metal lamp posts to retain heat. Occupied lamp posts exhibited higher inside temperatures than unoccupied lamp posts in the late afternoon and evening, suggesting active thermoregulation by bees to maintain optimal nest temperature. This study added our understanding to the adaptability of stingless bees in increasingly urbanized environment, contributing to pollinator conservation and meliponiculture industry improvement.